Pengaruh Dry Heat Treatment dengan Penundaan Waktu Tanam Terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum Frutescens L.) - DARMAWAN, I KADE; NYANA, I DEWA NYOMAN; SIADI, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
The Effect of Dry Heat Treatment with Time Delay Planting on Plant Growth and Yield of Chili Pepper (Capsicum frutescens L.) Viral pathogens which cause disease is a major problem in reducing the production of chili pepper. The younger the plants are infected by the virus, the more severe symptoms of the disease caused. Based on this statement, it necessary to do a research that aims to determine the effect of Dry Heat Treatment with a delay time of planting on growth and yield of chili pepper. The research design used was a randomized block design with three treatments and nine replications. The treatments tested consists of Dry Heat Treatment with a delay time of planting (DHT + TT), Dry Heat Treatment (DHT), and control (NT). The growth variable and the yield that had been observed in these experiments were the plant height (cm), number of primary branches, leaf chlorophyll content, incidence of disease, and the yield (tons / ha). The results showed that Dry Heat Treatment with a delay time of planting (DHT + TT) provides better results in the cultivation of chili with 86.27 cm plant height increased by 106.83% compared with controls (NT), the number of branches 12.61 increased 41.53 % compared with controls (NT), and the yield 17.21 tons / ha increased by 256.87% compared with controls (NT).
Keywords: Chili pepper; virus; Dry Heat Treatment; delay planting time